EFFECTIVENESS OF LEARNING MATHEMATICS WITH CONTEXTUAL APPROACHES - SRI RAHMAYANTI; MAPILINDO; HENI SUBAGIHARTI; TUTI HERAWATI (CV KULTURA DIGITAL MEDIA, 2020)
This experimental study aims to determine the effectiveness of learning mathematics with a contextual approach in terms of understanding students' concepts. The sample of this study was the whole of the population, namely all classes IX MTSN 2 Asahant 2018/2019 school year with the number of students as many as 48 students distributed in 2 classes, namely classes IX-A and IX-B. Based on testing the hypothesis with a significance level of 5%, it was found that the percentage of students completing had exceeded 70%. The conclusion of this study is mathematics learning with an effective contextual approach in terms of understanding students' mathematical concepts.